1998
DOI: 10.1159/000027571
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ammonia on Olfactory Epithelium and Vomeronasal Organ Neuroepithelium of Rabbits

Abstract: In recent studies, the vomeronasal organ (VNO), although vestigial and with unknown function in humans, was reported to be present in almost every person examined. In rabbits, it is a well-developed organ, one lying on each side of the nasal septum. Histologically it was found to contain neuroepithelium which is considered an accessory olfactory system taking charge of an olfactory discrimination different from that of olfactory epithelium. Experimental removal of the VNO in male animals reduces reproductive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Our study showed that compared to normal housing conditions, confined conditions induced more VNO changes, suggesting that the accumulation of pollutant gases and dust could be one of the causes of these changes in farm animals. These findings are in agreement with those reported in nasal mucosa studies, and alterations in the nasal mucosa have been previously linked to environmental contaminants such as organic dust and natural gases, including ammonia and hydrogen sulfide [ 14 , 15 , 16 ]. The olfactory epithelium and the sensory epithelium are physiologically and anatomically similar [ 25 ], and it is possible to draw a parallel between these two structures and their responses to environmental conditions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study showed that compared to normal housing conditions, confined conditions induced more VNO changes, suggesting that the accumulation of pollutant gases and dust could be one of the causes of these changes in farm animals. These findings are in agreement with those reported in nasal mucosa studies, and alterations in the nasal mucosa have been previously linked to environmental contaminants such as organic dust and natural gases, including ammonia and hydrogen sulfide [ 14 , 15 , 16 ]. The olfactory epithelium and the sensory epithelium are physiologically and anatomically similar [ 25 ], and it is possible to draw a parallel between these two structures and their responses to environmental conditions.…”
Section: Discussionsupporting
confidence: 92%
“…The olfactory epithelium is strongly impacted by air pollutants in the closed housing environment of many farm species, such as pigs or rabbits [ 14 , 15 , 16 , 17 ]. The organic matter litter decomposition releases some pollutants, such as ammonia [ 18 , 19 , 20 ], responsible for nasal pathologies and contributes to the deterioration and inflammatory lesions of the nasal epithelium in mice [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is well-known that urine is able to activate the main olfactory system (CN I) in the nasal cavity. Possibly, CO 2 exposure can induce histopathological changes in the different nasal epitheliums, and comparative studies could be relevant to determine whether the VNO is more protected as suggested by Gaafar et al (1998).…”
Section: Discussionmentioning
confidence: 99%
“…Several inhalation studies have considered effects of toxic chemicals on olfactory functioning, but only one (Gaafar et al 1998) has examined the influence on the VNO. However, histopathological changes on the VNO in relation to toxic exposure could have a major ecological impact as intraspecies relationships can be disrupted.…”
Section: Introductionmentioning
confidence: 99%